Impact analysis on distance variation between patch antenna and metamaterial - Katiyar, P.; Mahadi, W.N.L.W. (2015)
Metamaterials are artificially engineered material having negative permittivity and permeability. Due to their negative constitutive parameters, metamaterials are capable of focusing incident electromagnetic energy called as beam focusing property. We have made use of beam focusing property of metamaterial to enhance antenna far-field gain. We have also conducted experimental study by varying the distance between patch antenna and metamaterial array to determine optimum distance. The distance is varied in seven steps of 35 mm. The far-field gain of antenna is increased by 4 dB when metamaterial is placed at 95 mm. The beamwidth of antenna reduces when loaded with metamaterial indicating beam sharpening. At 155 mm from patch antenna, the beamwidth reduces to 33.95 degrees and starts increasing as metamaterial is moved further away. The resonance frequency and bandwidth of antenna follows alternate increase and decrease pattern as the distance of metamaterial is increased, however, the impact is negligible. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:178-183, 2015